Hemodynamics of postexercise versus post-hot water immersion recovery - Francisco, M. A.; Colbert, C.; Larson, E, A.; Sieck, D. C.; Halliwill, J. R.; Minson, C. T. (Journal of Applied Physiology, 2021)
This study sought to compare the hemodynamics of the recovery periods following exercise versus hot water immersion. Twelve subjects (6 women, 22.7 ± 0.8 yr; body mass index: 21.8 ± 2.1 kg/m2) exercised for 60 min at 60% V?o2 peak or were immersed in 40.5°C water for 60 min on separate days, in random order. Measurements were made before, during, and for 60-min postintervention (i.e., recovery) and included heart rate, arterial pressure, core temperature, and subjective measures. Brachial and superficial femoral artery blood flows were assessed using Doppler ultrasonography and cardiac output was measured using the acetylene wash-in method. Internal temperature increased to a similar extent during exercise and hot water immersion. Cardiac output and mean arterial pressure were greater during exercise than during hot water immersion (both P < 0.01). Sustained reductions in mean arterial pressure compared with baseline were observed under both conditions during recovery (P < 0.001 vs. before each intervention). Cardiac output was similar during recovery between the interventions. Stroke volume was reduced throughout recovery following exercise, but not following hot water immersion (P < 0.01). Brachial artery retrograde shear was reduced following hot water immersion, but not following exercise (interaction; P = 0.035). Antegrade shear in the superficial femoral artery was elevated compared with baseline (P = 0.027) for 60 min following exercise, whereas it returned near baseline values (P = 0.564) by 40 min following hot water immersion. Many of the changes observed during the postexercise recovery period that are thought to contribute to long-term beneficial cardiovascular adaptations were also observed during the post hot water immersion recovery period.